The technology tide: Has IT hit the shores of social innovation? - Koh, Andrew (Institutional Knowledge at Singapore Management University, 2018)
“We want a nice colour and it must look modern.” That was the feedback some villagers gave during a design-thinking exercise regarding sanitation facilities. Although this took place several years ago, as part of my previous work in the international development sector, I remember the experience vividly. It struck me that most people—village-dwellers or Singaporeans alike—have similar aspirations for a better quality of living.